2020
DOI: 10.1371/journal.pone.0238477
|View full text |Cite
|
Sign up to set email alerts
|

KAT6A amplifications are associated with shorter progression-free survival and overall survival in patients with endometrial serous carcinoma

Abstract: Somatic copy number alterations (CNA) are common in endometrial serous carcinoma (ESC). We used the Tumor Cancer Genome Atlas Pan Cancer dataset (TCGA Pan Can) to explore the impact of somatic CNA and gene expression levels (mRNA) of cancer-related genes in ESC. Results were correlated with clinico-pathologic parameters such as age of onset, disease stage, progression-free survival (PFS) and overall survival (OS) (n = 108). 1,449 genes with recurrent somatic CNA were identified, observed in 10% or more tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…[ 16 , 17 , 18 ] Increasing data demonstrate that KAT6A also regulates tumor progression. [ 10 , 14 ] KAT6A amplification and/or overexpression in luminal subtype breast cancers promoted tumor growth. [ 15 , 20 ] However, the mechanism by which KAT6A drives breast cancer progression is still elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16 , 17 , 18 ] Increasing data demonstrate that KAT6A also regulates tumor progression. [ 10 , 14 ] KAT6A amplification and/or overexpression in luminal subtype breast cancers promoted tumor growth. [ 15 , 20 ] However, the mechanism by which KAT6A drives breast cancer progression is still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 10 , 11 , 12 ] While KAT6B is considered a tumor suppressor, [ 13 ] KAT6A exhibits a predominantly oncogenic function in a number of cancers, including leukemia, glioma, endometrial serous carcinoma, and breast cancer. [ 10 , 12 , 14 , 15 ] In acute myeloid leukemia, KAT6A undergoes changes including gene mutation and fusion with proteins resulting from chromosomal rearrangement. [ 16 , 17 , 18 , 19 ] Earlier studies showed that KAT6A is amplified and/or overexpressed in Luminal A, Luminal B, HER2 + , and TNBC/basal‐like subtype breast cancers, and its overexpression correlates with worse clinical outcome in ER + /HER2 − breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Increasing data demonstrate that KAT6A also regulates tumor progression. [10,14] KAT6A amplification and/or overexpression in luminal subtype breast cancers promoted tumor growth. [15,20] However, the mechanism by which KAT6A drives breast cancer progression is still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] While KAT6B is considered a tumor suppressor, [13] KAT6A exhibits a predominantly oncogenic function in a number of cancers, including leukemia, glioma, endometrial serous carcinoma, and breast cancer. [10,12,14,15] In acute myeloid leukemia, KAT6A undergoes changes including gene mutation and fusion with proteins resulting from chromosomal rearrangement. [16][17][18][19] Earlier studies showed that KAT6A is amplified and/or overexpressed in Luminal A, Luminal B, HER2 + , and TNBC/basal-like subtype breast cancers, and its overexpression correlates with worse clinical outcome in ER + /HER2 − breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…According to our results, among ovarian cancer patients, the median survival time of patients with CEBPA high expression is shorter than that of patients with CEBPA low expression, and the overexpression of CEBPA level constitutes a factor of poor prognosis of ovarian cancer patients. This may be due to the obvious carcinogenic effect of CEBPA in ovarian cancer ( 25 ). Clinicians can consider measuring the expression level of CEBPA when treating patients with ovarian cancer, which is helpful to evaluate the prognosis of patients and improve their living standards.…”
Section: Discussionmentioning
confidence: 99%